Cold ridge formation mechanisms on the Agulhas Bank (South Africa) as revealed by satellite-tracked drifters. (April 2023) - Hancke, Lisa; Roberts, Michael J.; Smeed, David; Jebri, Fatma
Abstract: The formation of the cold ridge, a seasonal mid-shelf upwelling feature on the Agulhas Bank, is investigated from a combination of satellite-tracked surface drifters, in situ current and temperature data, as well as satellite sea surface temperature (SST) and chlorophyll- a (Chl- a ). The observational data showed coastal upwelling along the Tsitsikamma coast to be induced by the easterly wind in austral summer, with a coexistent westward flowing coastal current. Under this wind and current regime, surface drifters moved west and onto the mid-shelf with the cold water, thereafter following the southward-curved 100 m isobath. Satellite observations in March–April 2008 showed increased south-westward advection of wind-driven upwelled water during an Agulhas Current intrusion that resulted in the formation of a classically shaped cold ridge. Also of interest was the passing of a Natal Pulse along the south-eastern shelf edge of the Agulhas Bank in July 2007. This generated a large cyclonic eddy in the Agulhas Bight with an attendant warm water plume that swept over the adjacent shelf. Two idle drifters positioned on the mid-shelf at the time, immediately west of the Natal Pulse, were rapidly advected offshore along the curved 100 m isobath, confirming the long-thought association of the cold ridge with an Agulhas Bight cyclone. A moored current meter adjacent to the Tsitsikamma coast (1.5 km offshore) showed the effect of the Natal Pulse on the nearshore. Drifter trajectories show accelerated south-westward flow on the offshore side of the cold ridge and recirculation towards the east on its shoreward side. These findings strongly support the Westward Transport Hypothesis where squid paralarvae are advected westward from the inshore breeding grounds, to the food maxima on the interior of the central Agulhas Bank, to improve their chances of survival and can therefore have important implications for the management of the South African chokka squid fishery.